Segmental bone defect of the femur: a clinical case of reconstruction with an osteoseptocutaneous fibular free flap with allograft - S. Fernandes, Goncalo; Corte-Real, Catarina; C. Mendes, João; C. Dias, Ricardo; Pires, João; Homem, Emanuel; Boavida, João; P. Lopes, António (International Journal of Research in Orthopaedics, 2026)
Segmental bone defects (SBD) of the distal femur present complex challenges in orthopedic surgery with various reconstruction methods available, such as fibular flaps. We present a case of a SBD of the distal femur reconstructed with an osteoseptocutaneous fibular free flap with allograft, as described by Capanna. A 25-year-old man suffered a Gustillo-Anderson-IIIA supraintercondylar fracture AO/OTA C2.3 with an SBD of the distal femur from a motorcycle accident. Initial treatment included closed reduction, internal fixation with percutaneous screws and osteotaxis. Subsequently, he underwent minimally invasive osteosynthesis. Reconstruction at 17 days post-injury involved a contralateral vascularized osteoseptocutaneous fibular free flap with allograft using the Capanna technique. The patient was allowed free range of motion, achieving 95º by 6 weeks postoperatively, and 120º by 7 months. Partial weight-bearing was allowed at 3 months postoperatively, progressing to full weight-bearing at 5 months. Radiographic graft integration was found at the 18 month re-evaluation. At 4 years the graft is integrated, and no complications were reported. SBDs of the femur pose a challenging entity. Among the various described reconstruction techniques, notable ones include arthroplasties, induced membrane technique (Masquelet), bone transport, allografts/autografts, and flaps. The use of the described technique increases integration rates despite donor site morbidity. Early percutaneous reduction and fixation of the distal femur articular component reduced the complexity of the subsequent procedure. The technique described by Capanna allows for reconstruction with structural support, possibly reducing the risk of non-union and fracture, and represents a valid alternative in SBDs >6 cm.